Overweight adolescents with type 2 diabetes have significantly higher lipoprotein abnormalities than those with type 1 diabetes. (May 2016) - Hanks, Lynae J.; Pelham, James Heath; Vaid, Shalini; Casazza, Krista; Ashraf, Ambika P.
Highlights: Compares dyslipidemia in overweight or obese adolescents by diabetes type. Standard lipid profile may overlook lipoprotein abnormalities in diabetes. Glycemic control moderates CVD risk especially in patients with type 2 diabetes. Patients with type 2 diabetes had higher occurrence of atherogenic dyslipidemia. Abstract: Aim: Diabetes-associated glucoregulatory derangements may precipitate atherogenesis in childhood and CVD risk, particularly with obesity. We aimed to delineate lipoprotein profile differences between children with type 1 and 2 diabetes who are overweight/obese. Methods: Data were obtained from electronic medical records of patients ≥85th BMI percentile with type 1 ( n  = 159) and type 2 ( n  = 77) diabetes, ages 12–19 y. Group differences were evaluated by correlations and general linear modeling analysis, adjusting for BMI, HbA1c, and diabetes duration. Results: There were no group differences in TC, LDL, or non-HDL. Fewer subjects with type 1 diabetes had low HDL (17 vs. 30%; P  < 0.05). While no difference in HbA1c level was observed between groups, HbA1c was positively correlated with TC ( P  ≤ 0.0001), LDL ( P  ≤ 0.0001), non-HDL ( P  ≤ 0.0001), ApoB100 ( P  ≤ 0.0001), and LDL pattern B ( P  ≤ 0.0001). In adjusted models, apoB100 (85.4 vs. 91.3 mg/dl; P  < 0.05) and incidence of LDL pattern B (21 vs. 42%; P  < 0.01) were lower in subjects with type 1 diabetes. BMI was inversely correlated with HDL, HDL-2 and HDL-3 (all P  ≤ 0.0001). The correlation of BMI with HDL-2 and HDL-3 were attenuated when evaluating subjects by diabetes type. Conclusions: Despite having no difference in absolute LDL levels, children with type 2 diabetes were more likely to have small, dense LDL particle pattern, higher apo B100 and lower total HDL, HDL-2, and HDL-3 fractions. Furthermore, poor glycemic control was associated with abnormal lipoprotein profiles in patients with both type 1 and 2 diabetes.